The Potential of ESD-Oriented Learning in Environmental Change Materials - Teguh Prakoso; Endah Rita Sulistya Dewi; Muhammad Syaipul Hayat (FKIP - Universitas Riau, 2026)
The issues of sustainability and environmental degradation require learning strategies that equip students with 21st-century knowledge, values, and skills. This study aims to analyze teachers' needs, the potential for implementing differentiated learning designs, understanding of ESD values, and schools' readiness to support its implementation. The study uses a qualitative descriptive method through a survey of 50 biology teachers from high schools in Semarang Regency, Semarang City, and Kendal. Data were collected through questionnaires, interviews, observations, and documentation, then analyzed using triangulation techniques in the form of data reduction, data presentation, and conclusion drawing and verification. The results showed that teachers had a high need for more effective and adaptive learning designs and viewed positively the potential application of differentiated learning in helping students understand environmental change material. In addition, teachers demonstrated a strong understanding of the importance of integrating ESD values into biology learning. The readiness of schools was also considered quite good, as evidenced by the availability of facilities and innovation spaces for teachers. Overall, the results of the study confirm that the implementation of ESD-oriented differentiated learning has great potential to be optimally applied because it is supported by teacher readiness, school support, and its relevance to the needs of contemporary biology learning.